Risk Factors For Stunting Incidents In Toddlers - Juwita, Ratna (LPPM Universitas Prima Nusantara Bukittinggi, 2024)
Background: Stunting can hinder physical growth, increase a child's susceptibility to diseases, and create barriers to cognitive development, potentially reducing intelligence and productivity in the future. The prevalence of stunting in Riau Province in 2022 was 17%. This figure does not meet the target set by the Medium-Term Development Plan (RPJM), which is 14% by 2024. In Purnama Sub-District, Dumai Barat District, the prevalence of stunting remains high, with 47 toodlers (30%) out of a total of 159 under-fives affected.Objective: This study aims to identify the risk factors associated with stunting in toodlers aged 24-59 months, including maternal and child characteristics, knowledge, maternal nutritional status during pregnancy, exclusive breastfeeding history, and basic immunization history.Methods: This research is a quantitative study with an analytical observational design using a case-control approach.Results: Statistical tests showed significant associations between maternal education (p-value 0.29), maternal chronic energy deficiency (KEK) during pregnancy (p-value 0.032), history of iron tablet consumption (p-value 0.002), exclusive breastfeeding (p-value 0.031), and basic immunization (p-value 0.019) with stunting in toodlers. No significant association was found between occupation (p-value 0.059) and maternal knowledge (p-value 0.073) with stunting in toodlers.Conclusion: The calculation of the Odds Ratio (OR) indicates that pregnant women with a history of chronic energy deficiency are three times more likely to have stunted toodlers compared to those without a history of chronic energy deficiency. Women who do not exclusively breastfeed are three times more likely to have stunted toodlers compared to those who exclusively breastfeed. Toodlers who do not receive complete immunization are 11 times more likely to experience stunting than those who receive complete immunization. In this study, immunization was found to have the greatest impact on the occurrence of stunting in under-fives in Purnama Sub-District, Dumai Barat District, after controlling for variables such as exclusive breastfeeding, maternal history of iron tablet consumption, maternal occupation, maternal knowledge, and maternal nutritional status during pregnancy.